Parent-child attachment mediates the association between parental conflict perceptions and suicide intention: a cross-sectional survey among middle school students in China - Wang, Jiana; Chen, Kun; Huang, Xinyuan; Jin, Zhiyu; He, Jing; Han, Bingsong; Feng, Lin; Meng, Nana; Yang, Cong; Yao, Pin; Li, Zhe (Frontiers in Public Health, 2024)
Adolescent suicide is a prevalent issue globally, with various factors contributing to this phenomenon. This study, conducted among middle school students in Liaoning Province, China, from April to May 2016, aimed to investigate these factors and their interrelationships to better understand the causes of adolescent suicide and provide evidence for its prevention. A cross-sectional survey was administered to 1028 students aged 10-19, using instruments such as the Behavior Questionnaire-Revised (SBQ-R), Children's Perception of Interparental Conflict Scale (CPIC), and revised version of Inventory of Parent Attachment (IPPA-R). Binary logistic regression analysis revealed that adolescents aged 10-14, those living in rural areas, those with strong perceptions of parental conflict, those with high mother-child attachment, those with high father-child attachment, and Left-Behind Children (LBC) were at high risk of suicide intention. Furthermore, parent-child attachment played a mediating role between two dimensions of parental conflict perception (resolved situations and response effect) and suicide intention. The study concludes that adolescents living in urban areas, young adolescents, LBCs, adolescents with a high level of parental conflict intensity, and those with low levels of parent-child attachment are at high risk of suicide intention. Interventions aimed at reducing family conflicts and improving parent-child relationships are recommended to decrease the incidence of adolescent suicide.